PENERAPAN METODE KEPELATIHAN CABANG OLAHRAGA PERMAINAN DI SURAKARTA - Umar, Fadilah (Pendidikan Dan Kepelatihan Olahraga, 2010)
This research has the objective to determine: (1) Application of the method is training at sports clubs play in Surakarta in 2009. (2) Preparation of training programs in sports clubs play in Surakarta in 2009. The research method used is descriptive research method degan way surveys. The sample used was of trainers at sports clubs play in the city of Surakarta. Sample making techniques with random sampling. Total sample with 57 trainers from eight (8) sports such as football game, volleyball, basketball, futsal, tennis, table tennis, softball, baseball, and badminton. Research instrument uses a questionnaire with dichotomous response pattern (yes, no) with a score for each answer (yes) is given a score of "2" and the answer (not) be given a score of "1". Data was analyzed quantitatively with the aid of statistical analysis diskriptif, and presented in the form of a table containing the frequency and percentage of each grain instrument equipped with a descriptive explanation. Based on the results of data analysis can be concluded that: (1) Coaches sports club game in Surakarta in the year 2009 has been implemented is training with the right method because in the process of daily exercise some exercise principles such as emphasis on the principle of individual loads, progressive loading, variations in practice , high discipline, balance-recovery relief work, and the principle of correction and the evaluation is conducted properly. (2) training program composed of trainers of sports clubs play in Surakarta in 2009 was good, because most training programs have been prepared with a clear term of the program, the program adjusted the level or levels of athletes, containing technical training, containing all components exercise of physical conditions (such as strength training, endurance, speed, agility and flexibility), containing training tactics and includes forms of mental exercise.